Does Financial Tranquility Call for Stringent Regulation? - Basak, Deepal (IMF Working Papers; Working Paper ;, 2018)
Consistent with the Minsky hypothesis and the 'volatility paradox' (Brunnermeier and Sannikov, 2014), recent empirical evidence suggests that financial crises tend to follow prolonged periods of financial stability and investor optimism. But does financial tranquility always call for more stringent regulation over time? We examine this question using a simple portfolio choice model that features the interaction between learning and externality. We evaluate the potential of a macroprudential policy to restore efficiency, and characterize the necessary and sufficient condition for the countercyclicality of the optimal regulation/macroprudential policy. Our paper implies that policymakers should not only consider the cyclical indicators 'on the surface' (for example, credit growth), but also closely examine the deep structural change of the resilience of the system. The paper also highlights the importance of assigning the macroprudential policy function to independent agencies with technical expertise.